From Energy Blues to Green Energy: Options Before Pakistan (The Pakistan Development Review, 2014)
Energy crisis in Pakistan had been brewing long before it became an important national issue with the potential to significantly affect the outcome of general elections of 2013. The looming crisis of depleting non-renewable energy sources combined with a feeble economy has lent a new urgency to the search for an energy mix which is sustainable, economically viable and environmentally least hazardous. Fossil fuels with their known adverse environmental impacts dominate the current energy mix of Pakistan. The renewable energy sources remain underutilised despite being cost effective and less hazardous for the environment. A substantial amount of literature has highlighted various dimensions of existing energy sources in Pakistan with a particular emphasis on the environmental impact, the sustainability and the efficiency of various energy sources [see Asif (2009); Basir, et al. (2013); Bhutto, et al. (2012); Mirza, et al. (2009, 2008, 2003); Muneer and Asif (2007); Sheikh (2010) for example]. This study analyses the environmental impact, economic feasibility and efficiency of various energy sources subject to various economic and noneconomic constraints. Section 2 discusses energy security by reviewing various tapped and untapped energy sources besides analysing current energy mix and its future prospects. Section 3 highlights the interaction of energy use and environment. Section 4 discusses two approaches to assess the feasibility of an energy mix: disaggregated and aggregated. The latter approach makes a multidimensional comparison of all the energy sources discussed in this study. Section 5 consists of discussion and concluding remarks.